VALIDITY OF ASSESSMENT SHEETS FOR IDENTIFYING CONCEPTIONS AND ARGUMENTATION SKILLS IN CHEMICAL EQUILIBRIUM MATERIALS - Setyorini, Meyla Dewi; Rahcmadhaniar, Reta Nareswari; Naimah, Kholifatul; Novita, Dian (JCER (Journal of Chemistry Education Research), 2024)
This research aims to determine the validity of the conceptual identification assessment sheet and argumentation skills on chemical equilibrium material. This research uses the Research and Development type of research. The development model uses the ADDIE model by applying the Analyze, Design and Develop stages. The research subject is SMAN 16 Surabaya. Later, this research will use qualitative and quantitative data analysis. The validation results of the product validity assessment show that the data on the material aspect is in the very good category which is get mode score 4, the construct aspect is in the good category which is get mode score 3, and the language aspect is in the good category which is get mode score 4. The results of the teacher's response to the assessment instruments developed are good and can be used.